PERAN KEPALA SEKOLAH DALAM MEMBENTUK KEMANDIRIAN DAN AKHLAK ANAK MELALUI PROGRAM PARENTING DI RA RIZQI PAMULANG - Khasnah Syaidah; Kerwanto, Kerwanto; Maulana Urip (LPPM Institut Nida El-Adabi, 2025)
This study aims to examine the role of the principal in parenting programs as an effort to shape an independent and virtuous generation at RA Rizqi. The focus of the research is directed toward how the principal’s leadership is able to integrate parental involvement with the vision of early childhood education. The study employs a qualitative approach with a descriptive method to portray phenomena naturally based on field data. Data collection techniques include interviews, observations, and document analysis. The qualitative descriptive method was chosen to describe the forms, activities, characteristics, and relationships of the phenomena under study, while simultaneously developing theory from field findings. The research was conducted at RA Rizqi Pamulang. The results affirm the central role of the RA Rizqi principal in managing parenting programs as an integral part of early childhood education. The principal functions not only as an institutional manager but also as a moral leader who directs parental involvement to align with the school’s vision. The parenting program is designed to foster children’s independence through habituation of simple activities and to instill noble character through daily practices. The success of the program is supported by the commitment of the principal, teachers, and parental participation, despite challenges such as limited time and differences in parenting styles. Communication efforts and training carried out by the principal demonstrate a significant contribution to the emergence of an independent and virtuous generation.